NILAI DIAGNOSTIK RASIO LINGKAR PINGGANG / TINGGI TUBUH TERHADAP RISIKO PENYAKIT KARDIOVASKULER PADA ORANG DEWASA - Laeli Ardiani Putri; Neni Trilusiana; Hasanah Mumpuni (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose : This study aimed to determine the diagnostic strength, optimal cut off point and diagnostic value of waist circumference / body height ratio in detecting the risk of cardiovascular disease in adults with Frammingham Risk Score (FRS).  Method: This study is a cross sectional research design using secondary data from the Fourth Wave of the Indonesian Family Life Survey 4 (IFLS 4). Subject selection uses the total sampling method, so that the entire study population that matches the inculution and exclusion criteria will be the subject of this study. The number of research subjects that fit the inclusion and exclusion criteria are 9,103 people. This research uses ROC analysis, with the gold standard is the risk of cardiovascular disease based on FRS and the independent variable is RLPTTB. Results: Based on sex, the risk of cardiovascular disease in the moderate category was higher in men (80.54%) compared to women (30.23%). AUC RLPTTB value in male subjects was 0.5817 (95% CI 0.5610-0.624), while the AUC value in female subjects was 0.5904 (CI 0.5727-0.6084). The optimal cut off point in male subjects is 0.5249 (sens = 0.3549; spe = 0.7626), while the cut point in female subjects is 0.5796 (sens = 0.4382; spe = 0.7024). Conclusion: The RLPTTB cut-off value based on this study is 0.5249 and 0.5796, so the health message that can be given to the public to prevent the risk of cardiovascular disease is keep your waistline less than half your height